EVALUASI KEBIJAKAN REHABILITASI HUTAN MANGROVE DI PESISIR SULAWESI TENGGARA DALAM RANGKA PELESTARIAN LINGKUNGAN*) - Asramid Yasin (Jurnal Green Growth dan Manajemen Lingkungan, 2013)
This study is aim at evaluating the rehabilitation of mangrove forests in Southeast Sulawesi (Konawe Selatan and Kolaka) are compatible with the Permenhut No.P.70/Menhut-II/2008). The research was conducted in coastal Southeast Sulawesi consists of 2 locations with 4 respondents. This research is a qualitative descriptive type of policy. Data were collected by means of observation, interviews, and document analysis. The results indicate the implementation of policies of the Minister of Forestry (Permenhut No.P.70/Menhut-II/2008) views of realization in the region of Southeast Sulawesi Province namely Konawe Selatan sub Desa Tinanggea Akuni, more than half (70%) are not in accordance with Permenhut No.P.70/Menhut-II/2008, while the implementation of the policy of the Minister of Forestry (Permenhut No.P.70/Menhut-II/2008) views of realization in the region of Southeast Sulawesi Province namely Kolaka Sub Pomalaa Sub Harapan coastal, half (53%) does not match with the Permenhut No.P.70/Menhut-II/2008.